A QCD sum rule study of Theta(+) in nuclear matter - Navarra, F. S.; Nielsen, M.; Tsushima, K. (Elsevier B.V., 2005)
We consider a [ud](2)(s) over bar current, in the finite-density QCD sum rule approach, to investigate the scalar and vector self-energies of the recently observed pentaquark state Theta(+)(1540), propagating in nuclear matter. We find that, opposite to what was obtained for the nucleon, the vector self-energy is negative, and the scalar self-energy is positive. There is a substantial cancellation between them resulting in an attractive net self-energy of the same order as in the nucleon case. (C) 2004 Elsevier B.V. All rights reserved.